STRUCTURE MODELLING AND CATION PARTITIONING OF SPINEL SOLID SOLUTIONS AT HIGH T,P CONDITIONS - Lavina B.; Salviulo G.; Giusta A.D. (My University, 2004)
This paper presents evaluation of cation distributions from diffraction data collected at high T, P, and is an extension of the spinel structure modelling procedure by Lavina et al. (2002). Optimised cation-to-oxygen distances are modified for thermal expansion and compressibility at T and P of interest following Hazen and Prewitt (1977) and Hazen and Yang (1999). The procedure is applied to literature data concerning hercynite, spinel s.s., Zn aluminate, Zn ferrite, magnetite and the (Fe3O4)1-x(MgAl2O4)x join. Calculated cation distribution is strongly affected by standard deviations in cell parameters and oxygen coordinates. The underestimated values often reported in the literature for powder profile refinements may strongly affect the cation distribution; however, if standard deviations are increased to physically realistic values, consistent results are obtained. For P up to 10 GPa, reasonable evaluations of cation distribution are obtained for spinel s.s., Zn aluminate and magnetite, whereas for Zn ferrite they are limited to 1.8 GPa. For P beyond 10 GPa, compressibility cannot be assumed to be linear; the relationship between cell parameter and pressure is well-defined, but the inaccuracy of oxygen coordinate prevents simple modelling of bond distances with pressure.
Keywords: SPINEL; CATION DISTRIBUTION; THERMAL EXPANSION; COMPRESSIBILITY